2021
DOI: 10.1016/j.ejca.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Radical radiotherapy for paediatric solid tumour metastases: An overview of current European protocols and outcomes of a SIOPE multicenter survey

Abstract: Purpose/objective: About 20% of children with solid tumours (ST) present with distant metastases (DM). Evidence regarding the use of radical radiotherapy of these DM is sparse and open for personal interpretation.The aim of this survey was to review European protocols and to map current practice regarding the irradiation of DM across SIOPE-affiliated countries. Materials/methods: Radiotherapy guidelines for metastatic sites (bone, brain, distant lymph nodes, lung and liver) in eight European protocols for rhab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Finally, a small study by Sangthawan et al was reviewed; it was not found in our primary literature search but was identified from a prior systematic review [40] . This study evaluated 20 patients who received radiation to residual mIBG-positive sites of disease.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a small study by Sangthawan et al was reviewed; it was not found in our primary literature search but was identified from a prior systematic review [40] . This study evaluated 20 patients who received radiation to residual mIBG-positive sites of disease.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprising, hypoxic tumor subvolumes have been correlated with tumor evasion signatures such as tumoral immune escape, proliferation, mutational status and stemness [23] , [24] , [27] . In general, cancer stem cells represent a tumor subpopulation responsible for tumor metastasis and resistance to radiotherapy, ultimately leading to tumor relapse [28] , [29] , [30] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey across leading European paediatric radiotherapy centres unveiled both consistencies and differences regarding the radiotherapy approach with curative intent on metastatic sites, especially regarding patient selection and treatment characteristics [4]. A growing interest in hypofractionation was noticed, but prescription doses and fractionation schedules are currently mainly based on local experience and institutional protocols [4].…”
mentioning
confidence: 99%
“…Moreover, in current European paediatric solid tumour protocols, hypofractionation is sporadically recommended [5][6][7][8]. Across the respondents of the survey, an urgent need for consensus on the total and fraction dose per site, age group and disease category was expressed [4].…”
mentioning
confidence: 99%